The treatment effects of Trametes Robiniophila Murr against colorectal cancer: A mini-review - Li, Bo; Cao, Qian; Liu, Zhuo (Frontiers in Medicine, 2022)
Colorectal cancer (CRC) is a worldwide disease threatening people’s lives. Surgery and chemotherapy are still the main methods for CRC treatment. However, the side effects and chemotherapeutic drug resistance restrict the application of chemotherapy. Trametes Robiniophila Murr, also known as Huaier, is a traditional Chinese medicine that has been used for more than 1600 years. Huaier extracts have promising anti-cancer effects on hepatoma, breast cancer, and gastric cancer. Nowadays, the tumor inhibition of Huaier on CRC has attracted more and more attention. This review mainly provides the possible anti-tumor mechanisms of Huaier for CRC treatment in apoptosis and inhibiting proliferation of tumor cells, preventing epithelial-mesenchymal transformation (EMT), weakening proliferation and differentiation of CRC stem cells, decreasing the vessel density in tumor tissues, and enhancing the immune system and chemotherapeutic efficacy. Huaier extract may be a good candidate for CRC treatment, especially when combined with other chemotherapeutic agents.